PROBLEMATIKA PERNIKAHAN DINI: PENGARUHNYA DI DESA TANJUNGREJO KECAMATAN WULUHAN KABUPATEN JEMBER - Dea Opie Pancaraningrum; Salsabillah Rizqi Fihru Amani Fatikhah; Dela Adelia Puspita (CV. ADIBA AISHA AMIRA, 2023)
In the process of development, a person needs a life partner to give children and grandchildren according to everything that has been desired. Marriage can be defined as a way to create a harmonious and eternal household based on God Almighty. Marriage has a sacred meaning both morally, socially, and religiously as well as the state. Cases of early marriage that occur in Indonesia can be classified in the very high category, because Indonesia is ranked 2nd in ASEAN and 8th in the world for cases of early marriage. In Jember alone divorce cases reach 5000 cases a year, and most of the factors are due to the high rate of early marriage. Tanjungrejo is one of the villages located in the southern part of Jember Regency. In this village, early marriage is considered quite popular, almost all residents marry early. It is not surprising that those who marry over the age of 22 are considered unsolicited, especially for women who are considered old maids. The method used in this study is a qualitative research method. The phenomenon of early marriage in Tanjungrejo Village, which can be said to be quite a lot, has had a lot of influence and impact on those who do it and on the surrounding community. In this study, researchers used Max Weber's theory, namely the theory of social action. Factors supporting the existence of early marriage also cause impacts that are quite worrying so that this should get more attention